Uma história da constituição da matemática do colégio no cotidiano escolar - Otone, Maryneusa Cordeiro (2011)
This research examines a period in the history of mathematics education in Brazil. It s focus is restricted to the decades of 1930-50, a period which had defined the mathematics to be taught at the collegiate level, that currently called High School. The research considers the theoretical and methodological contributions from cultural history, particularly the contributions from history of school subjects. Fundamented on the view of the history of school subjects discussed by Dominique Julia and Andre Chervel, and the concept of ownership, characterized by Roger Chartier, this work emphasizes the study of historical sources from the school archives. The project takes as sources of research documents found in archives of the Faculty of Medicine School of São Paulo, Faculty of Law Largo São Francisco, Polytechnic School of São Paulo, São Paulo Stock of the College as well as personal files from teachers of mathematics that worked at Polytechnic School of São Paulo and São Paulo College. The work also uses educational legislation. We can cite as sources of this research school documents such as daily class diaries, tests, and minute book for teachers in addition to legislation relevant to the period studied. The research seeks to answer the following question: How was the College of Mathematics in their daily school? As developments on this issue have other questions: How were the contents of mathematics composed in school life of the College during the 1930 to 1950 decades at the Institutes of the University of São Paulo and São Paulo College? What were these contents during the decades of 1930-1950? The research examines the extension to which the proposed changes to the teaching of Mathematics at College, through the Reformation and Reformation Francisco Campos Capanema as amended by Ordinance 1951, respectively were appropriate and implemented at the University of São Paulo and the College of the Capital São Paulo State, during the 1930, 1940 and 1950. This research seeks to make a contribution to the history of mathematics education in Brazil